Acceptability and accessibility of child nutrition interventions: fathers' perspectives from survey and interview studies - Elena Jansen; Holly Harris; Lynne Daniels; Karen Thorpe; Tony Rossi (BMC, 2018)
Abstract Background Against a background of changing family structures and socioeconomic demands in contemporary families, fathers are more actively engaged in meal preparation and feeding of their children, yet in research studies targeting improvement in nutrition and feeding practices fathers are under-represented. Among possible explanations for this bias are acceptability of research projects and accessibility to male research participants. The aims of this study were to identify (i) fathers' preferences for participation in child nutrition research and interventions and (ii) the potential to recruit fathers through their workplaces with the possibility of delivering interventions through those workplaces. Methods This paper draws on two independent yet linked studies that explored fathers' roles in family feeding, and intervention studies aimed at supporting father's dietary knowledge and feeding practices. For Study 1 (conducted first) secondary data analysis was conducted on survey data (n = 463 fathers of preschool children) to determine preferences related to type of program, delivery mode, and location and timing. For Study 2 six focus groups and one individual interview were conducted with n = 28 fathers to determine acceptability of recruitment of fathers working in traditionally blue-collar occupations and service industries (as defined by the Australian Bureau of Statistics) and potential of intervention delivery through their workplaces. Results Fathers were engaged in child feeding and indeed sought nutrition-related information. Fathers indicated a preference for family-focused and online delivery of interventions. Whilst potential to recruit through blue-collar workplaces was evident, participants were divided in their views about the acceptability of interventions conducted through the workplace. There was a sense of support for the logic of such interventions but the focus group participants in this study showed only modest enthusiasm for the idea. Conclusions With limited support for the workplace as an intervention setting, further systematic exploration of technology-based intervention design and engagement is warranted. Based on findings, interventions should target a) content that is focused on the family and how to make changes at the family level, rather than the father individually; and b) online delivery, such as Apps or online video chat sessions, for convenience and to facilitate sharing of information with family members.